Trusted Data Travel Blogs Information Focusing on Followers - Zulkefli, N.A.B.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
In everyday circumstances, we always search for the best method to find results that we may see as accurate or efficient. However, the question is how do we trust the information? Do we easily use the result without first identifying the trustworthiness? In this paper, we will discuss the issue of trustworthiness especially the information sharing based on user experience. We identify new alternative information source that is followers where we can determine the trustworthiness of particular information. In our case study, we focus on the travel blog data as the travel information is one of the most sharing experiences in the Internet. We found that followers give better effect on trustworthiness. The more followers there are in a blog, the more value of trust is instilled in the blog and the trust value is supported by some new interesting findings which we shall discuss in the discussion section. © 2016 IEEE.